Motivasi Whistleblower Sebagai Upaya Pencegahan dan Pendeteksian Fraud Pada Sektor Pemerintah Indonesia Dengan Prinsip Amar Ma’ruf Nahi Mungkar - Aulia Nur Azizah; Mohamad Djasuli (Jurnal Ekonomika Dan Bisnis (JEBS), 2022)
The purpose of this study is to find out how the influence of the principle of amar ma'ruf nahi mungkar influences whistleblower motivation to prevent and detect fraud in the Indonesian government sector. This research combines qualitative research methodology with literacy study methods. The findings of this study indicate that the principle of amar ma'ruf nahi mungkar is seen as being able to inspire a reporter (whistleblower) to prevent and detect financial fraud that they find. With the development of an understanding of religious principles by one of the whistleblowers such as Amar ma'ruf Nahi munkar this will encourage individuals to act and conduct in conformity with the law. This will increase the motivation and confidence of whistleblowers to prevent and detect fraud in order to prevent losses due to fraud in the Indonesian government sector.